APPLYING OONN TO SOLVE MAP-COLORING PROBLEM - 余道衡; 贾积有 (Journal of Electronics(China), 1993)
<正> For solving the map-coloring problems,this paper presents an energy function,amore effective dynamic equation and a more simple convergence condition.For the first time westudy the map-coloring problems in the way of connecting discrete Hopfield neural network withthe orthogonal optimization,and as a practical example,a color map of China is given.
Keywords: Map-coloring problem; Hopfield neural network; Orthogonal optimization